Напрямки дослідження професійної ідентичності - Макарова, О. П.; Makarova, O. P.; ORCID: http://orcid.org/0000-0002-5480-5942; Мілорадова, Н. Е.; Miloradovа, N. E.; ORCID: http://orcid.org/0000-0002-0716-9736 (Вісник Національного університету оборони України. - 2014. - № 3 (40). - С. 268-272, 2014)
Стаття присвячена аналізу основних напрямків дослідження професійної ідентичності як інтегративного поняття. Розглядаються питання визначення поняття «професійна ідентичність» в межах різних підходів. Автором проводиться аналіз цього феномену з позиції взаємозв’язку когнітивних, мотиваційних, ціннісних характеристик особистості, що забезпечують орієнтацію в світі професії та дозволяють реалізувати себе, свій особистісний потенціал в професійній діяльності; сприяють прогнозуванню перспектив розвитку фахівця.

The article is dedicated to the analysis of the main ways of research the professional identity as integrative concept. It touches upon the issues of definition the concept “professional identity” within different approaches. The author analyses this phenomenon from the position of the correlation of cognitive, motivative and valuable characteristics of a person, that provides the orientation in the professional world and allows implementing yourself, your personal potential in the professional activity; promoting the prediction of specialist’s development prospects. The author gives an analysis of the approaches in western and native psychology as to methods of professional identity research within qualitative and quantitative review. It is given the examples of complex approach to this phenomenon studying and it is defined, that researching the professional identity is the complicated way of combination the qualitative and quantitative methods, results of which promote the forming the integral and system view at this phenomenon. The author points out that professional identity is a very important index of professional self-development.

Статья посвящена анализу основных направлений в исследовании профессиональной идентичности как интегративного понятия. Рассматриваются вопросы определения понятия «профессиональная идентичность» в рамках различных подходов. Автором проводится анализ этого феномена с позиции взаимосвязи когнитивных, мотивационных, ценностных характеристик личности, обеспечивающих ориентацию в мире профессии и позволяющих реализовать себя, свой личностный потенциал в профессиональной деятельности; способствующих прогнозированию перспектив развития специалиста.
Ways of research the professional identity
Макарова О. П. Напрямки дослідження професійної ідентичності / Макарова О. П., Мілорадова Н. Е. // Вісник Національного університету оборони України. - 2014. - № 3 (40). - С. 268-272.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; ідентичність; професійна ідентичність; професійна Я-концепція; професійне становлення; Я-концепція; идентичность; профессиональная идентичность; профессиональная Я-концепция; Я-концепция; профессиональное становление; identify; professional identity; professional self-conception; professional establishment; self-conception